A rapid prediction technology for the outburst risk of coal uncovered in crosscuts and shafts and its application in the Panyi Coal Mine in Huainan, China. Issue 2 (3rd April 2018) - Chen, Yujia; Li, Xiaowei; Tang, Jun; Yang, Dingding; Jiang, Chenglin
Abstract: In this study, we propose a set of rapid prediction technologies for the outburst risk of coal uncovering in crosscuts and shafts (CUCS). These technologies are needed because of the ideal model to uncover coal in crosscuts and the law that coal seam outburst intensity increases as the initial expansion energy of released gas (IEERG) increases. Our technologies include rapid coal seam gas pressure determination under complex geological conditions, complete coal-core coring and the IEERG measurement. We successfully applied these technologies in the Panyi Coal Mine in Huainan. The field application results demonstrated that these technologies could accurately and rapidly measure coal seam gas pressure, greatly minimize human damages to coal samples in the coal coring process, and accurately predict outburst risks in CUCS.